The effect of fabric constructions on elastic behaviour and tension decay of compression garment - Idris, M. K. M.; Nasir, S. H.; Roslan, M. N. (2021)
Knitted fabrics used as compression garments are subjected to deformation due to various loads used to extend the fabrics during wear. The loads to extend the fabrics are influenced by fabric constructions, strain levels and fabric directions. This study investigates the elastic behaviour and tension decay of different knitted fabrics at different strain levels. The strain of fabrics was measured using a tensile testing machine, and each sample was cycled five times between zero and the specified strain to simulate the repeated use of compression garments. The elastic behaviour and the tension decay were evaluated in both length (wales) direction and width (course) directions of the fabrics. It was found that fabric constructions, strain levels, and fabric directions have a significant impact on the fabric load and the tension decay of fabrics (p<0.05)